Dang Dinh Ang: Nonlinear analysis and mechanics (on the occasion of his eightieth birthday) - Dao, Nguyen Van; Dung, Nguyen (Vietnam Journal of Mechanics, 2006)
Professor Dang Dinh Ang is having his eightieth birthday this year. In honor of the occasion, the Institute of Applied Mechanics and the Institute of Mechanics of The Vietnamese Academy of Science and Technology, and the Laboratoire de Mechanique des Solides, Ecole Polytechnique Paris, with the participation of Vietnam Society of Mathematics, Vietnam Association of Mechanics will jointly organize an International Conference on "Nonlinear Analysis and Engineering Mechanics Today" at the Institute of Applied Mechanics, Vietnamese Academy of Science and Technology, December 11-14, 2006 in Hochiminh City, Vietnam.